This is the plate : Utah food traditions - Edison, Carol A.; Eliason, Eric A. (Eric Alden), 1967-; McNeill, Lynne S. (University of Utah Press, 2020)
"This is a general interest work edited and compiled by three folklorists that looks at multiple cultural dimensions of foodways in Utah. The contributors to the collection are also predominantly, though not exclusively folklorists. Their subjects, then, particularly concern food and its production and consumption practices as everyday traditions, by which they mean forms of creative cultural sharing and communication, not some measure of age. They intend this book for a broad readership, and they also delve into mass-mediated and commercialized popular culture, whose boundary with folk, or vernacular, culture, especially when it comes to food, is often porous. In fact, they have already generated a substantial amount of popular media interest, particularly with regard to certain foods (such as fry sauce, Jell-O salads, or funeral potatoes) that are widely considered iconic Utah foods. While they deal with such foods, they seek to complicate the Utah menu with a much wider, multicultural range of topics and a broader, deeper folkloristic discussion"--